2019
DOI: 10.1088/1741-2552/ab33e4
|View full text |Cite
|
Sign up to set email alerts
|

VMD-based denoising methods for surface electromyography signals

Abstract: Objective. Since noise is inevitably introduced during the measurement process of surface electromyographic (sEMG) signals, two novel methods for denoising based on the variational mode decomposition (VMD) method were proposed in this work. Prior to this study, there has been no literature relating to how VMD is applied to sEMG denoising. Approach. The first proposed method uses the VMD method to decompose the signal into multiple variational mode functions (VMFs), each of which has its own center frequency an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 50 publications
(97 reference statements)
0
25
0
Order By: Relevance
“…Although EMD has many advantages, it also has disadvantages, including its sensitivity to noise and the fact that the frequency bands of the components may overlap each other [106]. To address issues of the EMD method, [107] have developed a new decomposition method called variational mode decomposition (VMD).…”
Section: Denoising After Variational Mode Decomposition (Vmd)mentioning
confidence: 99%
See 1 more Smart Citation
“…Although EMD has many advantages, it also has disadvantages, including its sensitivity to noise and the fact that the frequency bands of the components may overlap each other [106]. To address issues of the EMD method, [107] have developed a new decomposition method called variational mode decomposition (VMD).…”
Section: Denoising After Variational Mode Decomposition (Vmd)mentioning
confidence: 99%
“…Since the VMFs and their respective center frequency can be obtained from the model, the signal is reconstructed using the inverse Fourier transform. [106] compared their VMD-based methods to both the EMD-based and wavelet-based methods in terms of SNR and RMSE and demonstrated that both proposed methods performed better at denoising. Moreover, they showed that the VMD-SIT version was more effective than the VMD-WST in addition to producing a smoother and continuous signal.…”
Section: Denoising After Variational Mode Decomposition (Vmd)mentioning
confidence: 99%
“…Wavelet-based adaptive filters have been increasingly proposed for removal of ECG noise from EMG recordings of various muscles, including the diaphragm, and with and without the use of extra channels for ECG recording [15][16][17]20,29,30]. This method performs well particularly when the ECG to EMG amplitude is high.…”
Section: Comparison With a Wavelet-based Adaptive Filter And Simulated Emg Signalmentioning
confidence: 99%
“…It has a sound theoretical foundation and is suitable for dealing with nonlinear and non-stationary series [38]. It decomposes the complex series into a series of approximately orthogonal simple modes and is popular in the fields of signal denoising [39], runoff forecasting [40], wind speed forecasting [41], etc. Thus, the complex PDI sequences are decomposed into simpler modes by VMD before being fed into GRU to improve the accuracy of prediction.…”
Section: Introductionmentioning
confidence: 99%